Suitability evaluation on material specifications and edible methods of Dendrobii Officinalis Caulis based on holistic polysaccharide marker - Zi-Jun Cao; Ka-Man Yip; Yi-Guo Jiang; Shi-Liang Ji; Jian-Qing Ruan; Cheng Wang; Hu-Biao Chen (BMC, 2020)
Abstract Background Dendrobii Officinalis Caulis (DC) is a well-known tonic herbal medicine worldwide and has favorable immunomodulatory activity. Various material specifications of DC are available in herbal markets, and DC is ingested by different edible methods. However, whether these specifications and edible methods are suitable or not remains unknown. Methods In this study, we evaluated the suitability of four material specifications (fresh stem, dried stem, fengdou and powder) and three edible methods (making tea, soup and medicinal liquor) based on holistic polysaccharide marker (HPM), the major polysaccharide components in DC. First, the HPMs were extracted from the four specifications of DC by the three edible methods in different conditions. Second, qualitative and quantitative characterization of the extracted HPMs was performed using high performance gel permeation chromatography (HPGPC). Third, immunomodulatory activities of the extracted HPMs were evaluated in vivo. Results The results showed that the HPMs were found to be quantitatively different from various specification of DC and edible methods. In vivo analysis indicated that the HPMs exerted positive effects on innate immune responses by increment in proliferation of splenocytes, secretion of IL-2 and cytotoxicity activity of NK cells. Moreover, the dosage amount of HPM should be defined as a certain range, but not the larger the better, for exerting strong immunological activities. Conclusion According to the both chemical and biological results, fengdou by boiling with water for 4 h is the most recommended specification and edible method for DC.